ANALYZING PLATFORM POWER: APP STORES AS INFRASTRUCTURAL PLATFORM SERVICES - Nieborg, David; Poell, Thomas; van Dijck, José (AoIR Selected Papers of Internet Research, 2019)
This paper examines how platform power is operationalized in the specific case of the iOS App Store. We take a first step in developing an analytical framework that critically examines the infrastructural power relations that constitute online platform ecosystems. Building on a relational understanding of power, we propose an analytical vocabulary to systematically interrogate the material power relations among the three main actors active in platform ecosystems: platform operators (e.g. Apple), third party institutions (e.g. app developers, businesses, governments), and end-users (i.e. individuals). To better differentiate among these three different actors in platform ecosystems, the paper proposes to study platform power at five expanding levels, similar to those of ecological ecosystems: individual actors, infrastructural platform services, company platform ecosystems, geopolitical platform ecosystems, and the global platform ecosystem. Studying infrastructural platform services, such as app stores, offers relevant insight into how globally operating platforms are able to set, steer, and bend rules and norms that impact individual actors on the local and national level. In the case of app stores, the paper shows that platform power is not casual or discursive, but highly strategic, uniform, and centralized. By interrogating the operationalization of platform power at the platform service level, the paper demonstrates that platform power is not a property of one platform itself, but a corollary of a platform’s function in the context of other platforms and actors in a dynamic ecosystem.